An enquiry into management of district central cooperative bank in Gujarat - Rathod, C. S. (Dept. of Cooperation, Faculty of Commerce, M.S. University of Baroda : Sole distributors, Good Companions, 1981)
Case study of Panchmahal District Central Cooperative Bank, 1976-1977, done under a research scheme of the M.S. University of Baroda.